Upaya Pemberdayan Masyarakat Melalui Pelatihan Tenun - Yuliza, Fera Fromita; Pamungkas, Alim Harun (JFACE: Journal of Family, Adult, and Early Childhood Education, 2019)
This research was written based on the existence of weaving activities in the community which aims to empower the community through skills activities so as to increase family income, improve welfare, create jobs reduce the level of urbanization. Indirectly can also preserve and maintain the Minangkabau culture to the next generation so that it does not become extinct. This is seen from the process of implementing community empowerment efforts through weaving training in Kampung Tenun. This study aims to illustrate how the effort of community empowerment through weaving training in the Batenggang Dibanang Nan Sahalai group that is being built in the village of Weaving Lintau. Community empowerment efforts start from the awareness process, mentoring process, evaluation process and follow-up process and its impacts. This type of research is research through a qualitative approach with the case study method. Data collection techniques used were observation, interview and documentary. Analysis of qualitative data used is data reduction, data presentation, and drawing conclusions. The researcher findings relate to the object of research while the results of the study relate to research subjects related to planning training activities, implementing weaving training activities and evaluating as well as follow-up activities.